The birth and death of the author : a multi-authored history of authorship in print - Power, Andrew J., 1977- (New York : Routledge, 2021)
The Birth and Death of the Author is a work about the changing nature of authorship as a concept. In eight specialist interventions by a diverse group of the finest international scholars it tells a history of print authorship in a set of author case studies from the fifteenth to the twenty-first century. The introduction surveys the prehistory of print authorship and sets the historical and theoretical framework that opens the discussion for the seven succeeding chapters. Engaging particularly with the history of the materials and technology of authorship it places this in conversation with the critical history of the author up to and beyond the crisis of Barthes' 'Death of the Author'. As a multi-authored history of authorship itself, each subsequent chapter takes a single author or work from every century since the advent of print and focuses in on the relationship between the author and the reader. Thus they explore the complexities of the concept of authorship in the works of Thomas Hoccleve and John Lydgate (Andrew Galloway, Cornell University), William Shakespeare and Christopher Marlowe (Rory Loughnane, University of Kent), John Taylor, "the Water Poet" (Edel Semple, University College Cork), Samuel Richardson (Natasha Simonova, University of Oxford), Herman Mellville (and his reluctant scrivener Bartleby') (William E. Engel, Sewanee, The University of the South), James Joyce (Brad Tuggle, University of Alabama), and Grant Morrison (Darragh Greene, University College Dublin).
OCLC-licensed vendor bibliographic record.
Keywords: Authorship -- History; LITERARY CRITICISM / General